Radiation-Stimulated Epigenetic Reprogramming of Adaptive-Response Genes in the Lung: An Evolutionary Gift for Mounting Adaptive Protection against Lung Cancer - Bobby R. Scott; Steven A. Belinsky; Shuguang Leng; Yong Lin; Julie A. Wilder; Leah A. Damiani (SAGE Publishing, 2009)
Humans are continuously exposed to low-level ionizing radiation from natural sources. However, harsher radiation environments persisted during our planet's early years and mammals survived via an evolutionary gift - a system of radiation-induced natural protective measures (adaptive protection) . This system includes antioxidants, DNA repair, apoptosis of severely damaged cells, epigenetically regulated apoptosis ( epiapoptosis ) pathways that selectively remove precancerous and other aberrant cells, and immunity against cancer. We propose a novel model in which the protective system is regulated at least in part via radiation-stress-stimulated epigenetic reprogramming ( epireprogramming ) of adaptive-response genes . High-dose radiation can promote epigenetically silencing of adaptive-response genes ( episilencing ), for example via promoter-associated DNA and/or histone methylation and/or histone deacetylation. Evidence is provided for low linear-energy-transfer (LET) radiation-activated natural protection (ANP) against high-LET alpha-radiation-induced lung cancer in plutonium-239 exposed rats and radon-progeny-exposed humans. Using a revised hormetic relative risk model for cancer induction that accounts for both epigenetic activation ( epiactivation ) and episilencing of genes, we demonstrate that, on average, >80% of alpha-radiation-induced rat lung cancers were prevented by chronic, low-rate gamma-ray ANP. Interestingly, lifetime exposure to residential radon at the Environmental Protection Agency's action level of 4 pCi L −1 appears to be associated with on average a > 60% reduction in lung cancer cases, rather than an increase. We have used underlined italics to indicate newly introduced terminology.